2017
DOI: 10.1016/j.difgeo.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Spectral invariants in Lagrangian Floer homology of open subset

Abstract: We define and investigate spectral invariants for Floer homology HF (H, U : M ) of an open subset U ⊂ M in T * M , defined by Kasturirangan and Oh as a direct limit of Floer homologies of approximations. We define a module structure product on HF (H, U : M ) and prove the triangle inequality for invariants with respect to this product. We also prove the continuity of these invariants and compare them with spectral invariants for periodic orbits case in T * M .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…In the proof of the previous theorems, we have shown that it is possible to construct quasi-morphisms using Lagrangian spectral numbers even in the case when we do not have a product in homology that ensures that they are subadditive. With the help of constructions in [8,9,10], we can apply these conclusions to the case when N is a manifold with a boundary.…”
Section: A Comment On Manifolds With Boundarymentioning
confidence: 94%
See 2 more Smart Citations
“…In the proof of the previous theorems, we have shown that it is possible to construct quasi-morphisms using Lagrangian spectral numbers even in the case when we do not have a product in homology that ensures that they are subadditive. With the help of constructions in [8,9,10], we can apply these conclusions to the case when N is a manifold with a boundary.…”
Section: A Comment On Manifolds With Boundarymentioning
confidence: 94%
“…It turns out that the upper limit of this sequence exists and it satisfies well known properties of partial quasimorphism. More precisely, if we define a map (9) σ…”
Section: Inclusion Induced By the Inclusion Map Of Chain Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [45,46] the previous construction is generalized to the case where is a submanifold with boundary in . The assumption that is closed can also be somewhat weakened [57].…”
Section: Lagrangian Boundary Conditionsmentioning
confidence: 99%
“…For periodic boundary conditions on closed symplectically aspherical symplectic manifolds, this construction is due to Schwarz [84], and for Lagrangian boundary conditions on a pair (zero-section, conormal bundle of a closed submanifold) in cotangent bundles, the construction is due to Oh [63,64]. There are several generalizations of these constructions, such as [25,45,46,54,55,57,61,63,64].…”
Section: Introductionmentioning
confidence: 99%